Formation of the content of bachelor's training in the specialty 011 Educational and pedagogical sciences - Bozhko, N. (Problems of Engineer-Pedagogical Education, 2023)
The article deals with the issue of forming a list of educational components of the educational program "Educational and Pedagogical Sciences" for training students majoring in the specialty 011 “Educational and Pedagogical Sciences” at the first bachelor's level. The lists of positions for which graduates of the educational program can be employed on the basis of the National Classification of Occupations and other regulatory documents, as well as education institutions in which they can work, are determined. The article analyzes the educational programs of Ukrainian higher education institutions for the training of bachelors in the specialty 011 “Educational and Pedagogical Sciences” and their educational focus. It is determined that all educational programs, regardless of their name, are aimed at training specialists in the field of education and pedagogy, social and educational, cultural and leisure activities. Based on the example of Ukrainian Engineering Pedagogics Academy, the article examines in detail the issues of forming the content of the educational program "Educational and Pedagogical Sciences" of the first bachelor's degree, taking into account the purpose of training and possible positions of pedagogical workers that its graduates can hold. Attention is focused on such positions of pedagogical workers as a teacher's assistant and a teacherorganizer; the regulatory documents (letters and orders of the Ministry of Education and Science) that regulate their activities are analyzed. The article highlights the absence of higher education standards in the specialty 011 "Educational and Pedagogical Sciences" and professional standards for these professions. A general description of the professions of a teacher's assistant (including inclusive and integrated education) and a teacher-organizer is given. The activities of these teaching professionals are analyzed, the qualification requirements for them and the labor functions they can perform are determined. The views of scientists on the definition of the concept of "professional competence" of a teacher's assistant and a teacher-organizer, as well as the components that make up its structure, are studied. The possibility of training a teacher's assistant and a teacher-organizer within one and the same educational program is proved, given identical qualification requirements for these specialists in most cases. Taking into account the knowledge that a teacher's assistant and a teacher-organizer should have, an indicative list of educational components to use in the process of studying at higher education institutions (which ensures their variability) and recommendations for its application (taking into account the educational focus of the program, stakeholder requirements, and opportunities of research and teaching staff) are determined.